The Impact of a Loss of Confidence in Emerging Market Economies to the World Economy: A Simulation with the G-Cubed Model - Mansur, Alfan (Jurnal Kajian Ekonomi dan Keuangan, 2017)
Risks in emerging market economies have considerably gone up as capital inflows have soared since the global financial crises in 2008. Once the advanced economies recover, especially in the US where its monetary stimulus ends, market expectations change. It may then potentially lead to sudden capital outflows from emerging economies which could lead to loss of confidence in the emerging market economies. To study the impacts of such event, this paper simulates with the G-Cubed Model. The results show that once financial shocks hit emerging market economies, it can produce critical real effects in the economic downturn which will last for a long period. The simulation also shows the strong interdependence between financial and real economies. In the emerging economies, expected future incomes and wealth fall, while the developed economies gain through the reallocation of investment. Another important channel of the shocks is through trade channel as most emerging market economies rely on imports for their production inputs.